Relationships between seed yield and yield components in narbon bean (Vicia narbonensis L.) by path analysis - Türk, Mevlüt; Çelik, Necmettin; Bayram, Gamze; Budakli, Emine (Bangladesh Journal of Botany, 2008)
Results of correlation analysis indicated that seed yield in narbon bean (Vicia narbonensis L.) was correlated positively with harvest index, biological yield, weight, number of seed and number of pod per plant and also plant height and number of plant per m2. Path coefficient analyses revealed that harvest index and biological yield had higher positive direct effects on seed yield than other variables. Stepwise multiple regression analysis showed that 95.1% of total variation in seed yield could be explained by the variation in harvest index, biological yield and plant height. Results suggest that harvest index and biological yield are primary selection criteria for improving seed yield in narbon bean.